FROM METAPHOR TO ACTION EMBODIED LANGUAGE COGNITION - Pilar Casado (Mètode Science Studies Journal, 2017)
The traditional theories that tried to explain how brain activity leads to cognition used the computer metaphor to describe the way the brain processes information codifying it into symbols that can combine following a finite set of rules. However, recent studies with updated paradigms that used neuroimaging techniques show that the brain activity registered when we observed a brain involved in some cognitive task are the same we would observe if that brain was immersed in perceptual, motor or emotional processing of the information handled for the task. In this article, we review the latest contributions to embodied cognition theories that provide a new approach to human cognition.